Bacteriophage-Based Techniques for Detection of Foodborne Pathogens - Rees, C. E.D.; Swift, B. M.C.; Botsaris, George (My University, 2014)
© 2014 Elsevier Ltd. All rights reserved. Bacteriophage have been used for many years as an established typing scheme for bacterial isolates recovered from food. More recently, there has also been a resurgence in interest in the use of bacteriophage as biocontrol agents in food. Although these two applications are well developed, this review focuses on the use of bacteriophage - or bacteriophage products - for the rapid detection of bacterial pathogens. Rapid detection methods that use both engineered (termed 'reporter phage') and nonengineered bacteriophages are described, along with the application of purified bacteriophage lysins in detection assays.
Keywords: Bacteriophage; Cell lysis; Detection; Lysin; Phage amplification; Rapid methods; Reporter phage